Low Cost and Portable Laboratory Kit for Practicum Learning of Air Conditioning Process in Vocational Education - Berman, Ega Taqwali; Hamidah, Ida; Mulyanti, Budi; Setiawan, Agus (Journal of Technical Education and Training, 2021)
The purpose of this research is to demonstrate low-cost and portable air conditioning practicum equipment for vocational education. The difference between our kits and other commercial products is their simple design and the components available in the market. So that this kit can be assembled by yourself because the price is affordable. This kit consists of the main components of a 4 inch diameter round air duct made of PVC, a blower, 5 temperature sensors, 5 humidity sensors, an air flow sensor, a refrigeration system, 2 electric heaters and an ultrasonic humidifier. In addition, this kit is relatively small with dimensions of 1500 x 600 x 700 mm and is easy to move and can be used in various places. Total analysis costs less than 3,000 USD, while commercially available offer prices are more than 5,000 USD. Thus the manufacture of this kit is suitable for developing countries with a lot of trial space and limited funding. The performance test results from this kit are also able to show psychometric processes that can be directly observed on the monitor display. In the future, this kit can be integrated with computer devices so that measurement data recording can be more accurate and automatically stored safely.